PERAN KELUARGA DALAM PENANGGULANGAN KENAKALAN REMAJA - Andi Syahraeni (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
Parents in Handling Juvenile Delinquency by means of prevention (prevention), namely instilling character from childhood in children, paying more attention to parents, inviting children to participate in community activities. The repressive way is to give advice and warnings and the curative way is to educate and take action. The inhibiting factors are the lack of supervision, the lack of education, and the child's association. Teenagers can control their behavior in daily life both in the family and in the community so that they do not behave in a deviant manner that has the potential to commit juvenile delinquency, as well as the efforts made by parents in overcoming juvenile delinquency so that adolescent behavior is better than before. It is hoped that parents can foster, guide, and keep an eye on their teenage children so that they don't make wrong associations that can make children commit juvenile delinquency which is able to disturb the surrounding.